Understanding christian-muslim relations past and present - Bennett, Clinton (Continuum International Publishing Group, 2008)
Offers an investigation into Christian-Muslim relations, highlighting the need for an understanding between the two communities in order develop universal peace and justice. This book investigates Islam's place in the world, Muslim aspirations vis-a-vis non-Muslims and the realities of how Christians perceive Muslims and Muslims Christians